The supervisory communication-commitment to work-group model: Example on a Malaysian organization - Mohamad, Bahtiar; Abu Bakar, Hassan; Mustaffa, Che Su (David Publishing Company, 2010)
This study examined the relationship between supervisory communication and commitment to work-group model in a particular Malaysian organization. We employed structural equation modeling (SEM) statistical procedures. We found that positive relationship communication, upward openness, negative relationship communication and job-relevant communication within superior-subordinate relationships have significant effect on group commitment. Consequences of this finding were discussed and elaborated in this article.